Urinary Tract Infections: Pediatric Primary Care Curriculum Podcast - Allison Reid Burks; Daniel Nicklas; Jason Owens; Tai Mara Lockspeiser; Danielle Soranno (Association of American Medical Colleges, 2016)
Abstract Introduction Demands on residents' time during training make it difficult for them to engage consistently with a primary care curriculum. In response to this, the emergency medicine and critical care fields have successfully utilized podcasting to the point where a recent study showed US emergency medicine residents ranked podcasts as the best use of their time for extracurricular education. Methods We produced a 30-minute podcast on urinary tract infections from a primary care perspective, based on descriptors from Entrustable Professional Activity 4, "Manage acute common illnesses in the ambulatory setting." A moderator, a primary care pediatrician, and a pediatric nephrologist used a loose script of salient points, allowing for a natural evolution of the dialogue. The podcast was distributed to residents via email, along with a 7-question survey. Results The survey was completed by 50 out of 84 residents. Ninety-two percent listened to all or part of the podcast, 98% found it educational, 93% enjoyed listening, and 74% felt more confident identifying and managing patients with possible urinary tract infections after listening. Ninety-six percent felt podcasts were a good alternative method for delivering this curriculum. One comment read, "This was great! It makes the information more accessible so that I can listen while working out or driving or just laying on the couch." Discussion Based on this success, we are producing additional podcasts and will strive to keep them under 20 minutes, provide key summary points at the end, and improve ease of access by utilizing an RSS (rich site summary) feed.